Factors Affecting Employee’s Retention: Integration of Situational Leadership With Social Exchange Theory - Xuecheng, Wei; Iqbal, Qaisar (Frontiers in Psychology, 2022)
Sketching on the Social Exchange Theory (SET), the present study aims to investigate the direct relationship between training and development, work environment and job satisfaction with employee retention. The contingent role of transformational leadership was also analysed under the Situational Leadership Theory (SLT). Accordingly, we collected data from 287 employees of SMEs in northern China by employing a convenience sampling approach, exhibiting a response rate of 57.40 per cent. The Partial Least Square- Structural Equation Modelling (PLS-SEM) analysis was then run to test the proposed hypotheses. The findings revealed a significant positive impact of training and development, work environment, and job satisfaction on employee retention. However, no moderating effect of transformational leadership was indicated on their direct relationship. This study has enriched the literature on employee retention and the leadership arena. To the best of the authors’ knowledge, there is no prior evidence concerning the study’s integrated relationship of the continuous variables. The implications and limitations were finally expressed at the end of this manuscript.